Study on Technology for Precision Correction of Land Survey Data based on Plotting Result Data and Feature Points - G. Zeng; S. Xie; J. Peng; M. Liu (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2014)
High‐precision land survey data is important foundation for fine management of land resources and enhancement of land use efficiency. The main method for land survey is remote sensing (RS) survey. However, the accuracy of data gained through this method is susceptible to image map, boundary interpretation, plotting process and other factors. To improve the accuracy, the method of precision correction of land investigation data that is based on high resolution image data with geometric correction model was discussed in detail. Technical test was conducted in some area of GuangZhou in China, and experimental results showed that the method can improve the accuracy of land survey data effectively.